2009
DOI: 10.1002/ajp.20742
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of organochlorine pesticides and metals in ring‐tailed lemurs (Lemur catta) at Beza Mahafaly Special Reserve, Madagascar

Abstract: Like most of Madagascar's endemic primates, ring-tailed lemurs (Lemur catta) face a number of threats to their survival. Although habitat loss is of greatest concern, other anthropogenic factors including environmental contamination may also affect lemur health and survival. In this study, we examined ring-tailed lemurs from the Beza Mahafaly Special Reserve (BMSR), southern Madagascar for exposure to organochlorine (OC) pesticides and metals and examined differences in contaminant concentrations between sexes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 71 publications
0
8
0
Order By: Relevance
“…Although cobalt values for several lemur species have been recorded Irwin et al, 2010;Junge et al, 2008], nickel values have not been determined for other lemur species, except as measured in hair of Lemur catta by Rainwater et al [2009]. Elevated levels of cobalt and nickel in indri at AFC indicate probable higher levels at that site.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Although cobalt values for several lemur species have been recorded Irwin et al, 2010;Junge et al, 2008], nickel values have not been determined for other lemur species, except as measured in hair of Lemur catta by Rainwater et al [2009]. Elevated levels of cobalt and nickel in indri at AFC indicate probable higher levels at that site.…”
Section: Discussionmentioning
confidence: 96%
“…The majority of primate pathogens will exert long-term, sublethal effects that can reduce population sustainability [Goldberg et al, 2008a], and the only way to document these changes is with consistent health monitoring. Health assessments have been completed on a number of lemur species [Clough, 2010;Dutton et al, 2003Dutton et al, , 2008Garell & Meyers, 1995;Irwin et al, 2010;Junge & Garrell, 1995;Junge & Louis, 2002, 2005a,b, 2007Junge et al, 2008;Miller et al, 2007;Raharivololona, 2006;Raharivololona & Ganzhorn, 2009, 2010Rainwater et al, 2009;Wright et al, 2009]. However, when compared with other primates, there is a need for more data on the impacts of human disturbance on lemur health as well as an expanded inventory of lemur parasites [Irwin & Raharison, 2009;Raharivololona & Ganzhorn, 2010].…”
Section: Introductionmentioning
confidence: 98%
“…Assessment of pesticide concentrations (e.g., Rainwater et al 2009) in geladas and other locust-eating fauna would help evaluate the extent to which the health and survival of these species are threatened by current locust management strategies. Our observations during the Guassa outbreak reinforce recent concerns regarding the potential environmental effects of locust control using traditional chemical insecticides and highlight the importance of increased emphasis on the development and use of biological agents for locust management (Lomer et al 2001;Hunter 2005).…”
Section: Discussionmentioning
confidence: 99%
“…A study by Engel et al (2010) reported low to moderate hair lead levels in rhesus macaques from the Swoyambhu temple in Kathmandu, Nepal. A second study on ring-tailed lemurs at Beza Mahafaly Special Reserve in Madagascar failed to detect lead in hair samples (Rainwater et al 2009). …”
Section: Wildlife As Indicators and Sentinels Of Environmental Contammentioning
confidence: 96%